The impacts of advance-order discounts on a three-echelon supply chain. (July 2020) - Yang, Feng; Niu, Qianyu; Kong, Junjun; Ang, Sheng
Highlights: We model a three-echelon supply chain with two advance-order discounts. Two-advance-order-discount model dominates no-advance-order-discount model. We compare two-advance-order-discount model with one-advance-order-discount model. The condition where upstream firms should put a constraint on the minimum advance order quantity is found. Two-advance-order-discount model with a minimum order quantity can coordinate the supply chain. Abstract: Rush orders are costly in supply chains because manufacturers incur higher production costs, while the production cost of advance orders is lower due to the relief of production pressure before the selling season. To motivate downstream firms to place an advance order, upstream firms often offer advance-order discounts. In a newsvendor setting, we consider a three-echelon supply with two advance-order discounts: one discount is between the manufacturer and the distributor, and the other is between the distributor and the retailer; we call this the two-advance-order-discount model. With two special cases, the one-advance-order-discount model and no-advance-order-discount model, as benchmarks, we investigate the implications of advance-order discounts on the three-echelon chain. We find that the two-advance-order-discount model dominates the no-advance-order-discount model. Compared with the one-advance-order-discount model, though the manufacturer and the distributor obtain lower profits, their conditional value-at-risk significantly decreases in the two-advance-order-discount model. Furthermore, we explore the two-advance-order-discount model with a minimum order quantity wherein there is a constraint on the minimum advance-order quantity, and discover that this model can coordinate the three-echelon supply chain. We also derive a condition under which upstream firms should constrain the minimum advance-order quantity.